STRATEGI PENGEMBANGAN WISATA MINAT KHUSUS BERBASIS RELIGI DAN MULTIKULTURAL DI DESA WISATA PESAREAN GUNUNG KAWI: ANALISIS POTENSI DAN TANTANGAN - Chintya Paramita Puspita; Andhi Supriyadi; Inda Citra Winda; Rumman Rumman; Duhita Fitri Anggraeny (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to analyze the development strategies for religion- and multiculturalism-based special-interest tourism in Pesarean Gunung Kawi Tourism Village, Malang Regency, with a focus on identifying the destination's potential and challenges. The growing interest in spiritual, authentic, and culturally grounded tourism experiences reflects a paradigm shift from mass tourism to special interest tourism. In this context, Gunung Kawi possesses unique characteristics as a religious destination evolving within a multicultural social environment. This study employs a qualitative approach with an ethnographic case study design. Data were collected through semi-structured interviews, participatory observation, and documentation involving tourism village managers, community leaders, local business actors, and tourists selected through purposive and snowball sampling techniques. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal four main themes: (1) religious tourism is understood as a spiritual practice integrating religious values, culture, and personal experience; (2) cultural and religious diversity forms an inclusive and harmonious multicultural tourism space; (3) tourists exhibit special interest tourism characteristics through intrinsic motivation, active involvement, and transformational experience; and (4) destination development faces challenges including visitor fluctuation, infrastructure limitations, and the risk of cultural commodification. This study contributes to strengthening the concept of religion- and multiculturalism-based special interest tourism within a sustainable tourism framework.